Challenges on Taxi Management in Kathmandu Valley: Taxi Drivers Perspectives - Devkota, Niranjan; Ghimire, Anshu; Bhandari, Udbodh; Parajuli, Seeprata; Poudel, Udaya (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2021)
Taxi as a means of transportation has been emerging as a handy option for people of any age for any occasion if they need to travel. Thus, this study aims to analyze challenges on taxi management in Kathmandu valley, Nepal, from the perspective of taxi drivers. A descriptive method is applied in the survey, and qualitative analysis is made among 386 taxi drivers of Kathmandu valley. The study's findings revealed that 77% of taxi drivers face challenges in the valley. Significant challenges arise from increasing private vehicles and easy access to public transportation, emergence of online vehicle service providers, government rules and regulations, and parking difficulties. Therefore, the study concludes that policymakers and responsible authorities should consider the strategy to improvise the overall taxi management system in the valley. This study can be useful to concerned authorities in taxi management services to make strategies for the betterment and to mitigate the challenges in the field. If the taxi management system got effective, that would be encouragement for other vehicle management.